Ehrlichia chaffeensis proteomic profiling reveals distinct expression patterns of infectious and replicating forms - Kondethimmanahalli, Chandramouli; Ganta, Roman R. (Frontiers in Cellular and Infection Microbiology, 2025)
Ehrlichia chaffeensis is a tick-transmitted rickettsial pathogen responsible for causing human monocytic ehrlichiosis (HME). The pathogen’s developmental cycle includes infectious dense-core cells (DCs) and non-infectious replicating cells (RCs). Defining the proteins crucial for the two growth forms is of fundamental importance in understanding the infection and replication process, which also aids in identifying novel therapeutic targets against HME and other related rickettsial diseases. E. chaffeensis organisms cultivated in a macrophage cell line were purified as DC and RC fractions and subjected to comprehensive quantitative proteome analysis. From triplicate sample analysis, we identified 195 proteins as commonly expressed in both the DC and RC forms, while an additional 189 proteins were recognized as exclusively expressed in the RC form. Equal numbers of commonly expressed proteins in the RC and DC forms and having substantially more proteins exclusively expressed in the metabolically active RC form may reflect specific functional priorities of E. chaffeensis supporting its replication within a phagosome. The high abundance of metabolic processes and transport proteins in the RC compared to the DC form may reflect its higher metabolic requirements and interactions with a host cell supporting its intraphagosomal replication. This study provides comprehensive proteome data for E. chaffeensis which will be valuable for a better understanding of protein expression dynamics during its infectious and replicating stages.